Digital Political Stage: An Analysis of the Hyperreality of Prabowo–Gibran’s Social Media Gimmick Campaign in the 2024 Election - Saputro, Moh. Adil; Prakasita, Ajeng Widya; Rahmat, M. Basuki; Fitria, Vany (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
Digital platforms have transformed political campaign models and created spaces where the boundaries between reality and illusion become blurred. This study analyzes the social media gimmick strategy used by the Prabowo-Gibran pair in the 2024 election, highlighting how the gimmick is not only a tool of political communication, but also builds hyperreality. Using the theoretical framework of simulacra and simulation from Jean Baudrillard, this study reveals how political communication strategies through gimmicks on social media can build a hyperreal image, where campaign elements become more